Studies on the TEG with changes in temperature difference and material properties - Alluri, Pavani Lakshmi; Alli, Daisy Rani; Reddy, DV Rama Koti (International Journal of Innovative Research and Scientific Studies, 2024)
The thermoelectric generators are solid-state devices that produce electricity. They are designed to harness unused energy, or “waste heat”. These devices were primarily utilized in military and space projects due to their reliability as a self-contained power source, requiring minimal maintenance. Additionally, they are environmentally sustainable and renewable sources of energy, emitting no air or noise pollution. According to research, Thermoelectric Generators (TEGs) have a relatively low efficiency rate of less than 5%. However, they hold the potential to effectively harness low-temperature waste heat, making them a promising energy source for the purpose of charging battery cells or super capacitors utilized in autonomous sensors. This study analyses the feasibility of generating electricity through segmented TEGs operating at temperatures below 296 K. Thermoelectric materials were studied to improve the conversion efficiency of the TEG. Furthermore, an investigation was conducted on the configuration of the thermoelectric generator. The COMSOL Metaphysics software is used to design and stimulate the segmented TEG model. This model is initially derived from an existing generator and is known for its accurate outcomes. The study revealed that using an alloy consisting of 75% Bi2Te3, and 25% as a substitute for the thermoelectric material PbSe0.5Te0.5, which led to a significant increase in conversion efficiency and output voltage. A segmented TEG model exhibited higher conversion efficiency. The model is subsequently refined by incorporating various modifications aimed at improving its conversion efficiency.